Marsupial Mitogenomics - Nilsson, Maria (Department of Cell and Organism Biology, Lund University, 2006)
The relationships of the mammalian infraclass Marsupialia have been investigated by phylogenetic analysis using completely sequenced mitochondrial genomes. The organisation and structure of the marsupial mitochondrial genomes deviates from the general mammalian structure. Several features, not known from other mammalian mitochondrial genomes have been shown to be present in all seven living marsupial orders. These features include among others RNA-editing, gene rearrangements and pseudogenes. The marsupial mitochondrial control region appears to be more conserved than that of mammals in general. The conserved sequence blocks present are longer and more conserved than in other mammalian groups. The phylogenetic analyses of the concatenated protein-coding genes of mitochondrial genomes support a basal division of marsupials into the cohorts Ameridelphia and Australidelphia. Australidelphia encompass the South American order Microbiotheria and all four Australian marsupial orders. Microbiotheria is solidly nested inside Australidelphia, which suggests that marsupials have colonised Australia in at least two lineages. Ameridelphia consist of the two other South American orders, but these share no close relationship. The resulting marsupial mitogenomic tree have been used to infer the marsupial divergence times with a relaxed molecular clock method. Almost all of the marsupial divergence times are estimated to have occurred after the Cretaceous-Tertiary boundary when the dinosaurs became extinct at 65 million years ago. This pattern deviates from that of placental mammals, where almost all divergence times have been estimated to have taken place before the Cretaceous-Tertiary boundary. The divergence time estimates of marsupials are congruent with the marsupial fossil record. The molecular divergence estimates are important for the understanding of the origin, pattern and timing of the marsupial dispersal over South America, Antarctica and Australia.